Patellar chondromalacia among adolescent athletes-A systematic review - Milanovic F; Aksovic N; Bjelica B; Topalovic N; Arsenovic M; Bukva B; Bardak S; Nikolic D (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2021)
Knee injuries, acute or chronic are one of the most often injuries in sport, both in adults and adolescents. They mostly occur in contact sports due to torsional and decelaration forces, causing around 80% painful knee conditions that disable sports performance. If chronic, they occur in the form of repetitive microtrauma that generates articular cartilage damage, producing cartilage softening and thinning and causing anterior knee pain. Etiological factors that are also associated with anterior knee pain in the form of patellar chondromalacia are idiopathic or post-traumatic patellar luxation and different types of femoral trochlear dysplasia. Repetitive trauma might cause cartilage fissures, fragmentation and necrosis so the patients can feel retropatellar pain, ussually after physical activities. Treatment of patellar chondromalacia is usually conservative but an early diagnosis (magnetic resonance imaging and arthroscopy) is essential in the prognosis of these patients.